Comparison of Success Rate of Estrus and Pregnancy between Laser Puncture and Intra Vaginal Progesterone Sponge in Bali Cattle - R. Tatang Santanu Adikara1 , Herry Agoes Hermadi2 , Warsito Sunaryo Hadi3 , Lita Rakhma Yustinasari4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
The purpose of this study was to find a method of determining laser models and intra vaginal progesteronesponge in Bali Cattle. An assessment was carried out at Sapi Loka Grati, Pasuruan, Indonesia. The parametersobserved included the symptoms of estrus, response of estrus, and the level of pregnancy. Twenty Balinesecows were divided at random in two groups. P1 treated with laser puncture at a certain point and P2 treatedwith 1.5 g of progesterone + 10 mg of estradiol benzoate intra vaginal sponge. The diagnosis of subsequentpregnancies was done by ultrasonographic examination on day 40th after artificial insemination (AI). Thelaser used in this study was a soft laser with power supply specifications as follows: 50 Hz, 220 Volts, 50Watts, ranging from 0.2 Joules to 0.5 Joules. These lasers include semiconductor lasers and laser probes.Three acupuncture points were used (GV 4, BL-22, and GV-2). Furthermore, the intra vaginal progesteronesponge used was made from silicone plastic similar to the drugs containing medroxyprogesterone acetate.Data testing was done by using the T-test. Results demonstrated that the P1 responses of estrus appeared onday 3rd, while P2 on day 9th. There was no significant difference (p >0.05) in the accumulation of estrus andpregnancy. In conclusion, estrus synchronization and pregnancy rate could be efficiently achieved in Balicattle using either laser puncture or intra vaginal progesterone sponge. However, laser puncture treatmentinduced more spread estrus with higher pregnancy rate.